RECURRENT OF TMPRSS2 GENETIC POLYMORPHISM AND ITS ROLE IN IRAQI PATIENTS WITH PROSTATE CANCER - K. A., Ammar; Altaee, M. F. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The role of transmembrane protease serine 2(TMPRSS2) in prostate carcinogenesis relies on overexpression of ETS transcription factors. The aim of this article was to investigate the association of TMPRSS2 polymorphism (rs12329760 (C)) with prostate cancer (PCa) in sample of Iraqi patients. One hundred and two individuals were involved in this study for the period from February – 2019 to February – 2020. The sample type was formalin fixed paraffin embedded tissue samples (FFPE), which involved fifty-six samples of pre-diagnosed patients with prostate cancer, aged between 48 and 86 years, and forty-six samples were found to be controls (healthy group) dependent on Prostate Gland integrity, which is the same age as in a group of patients. Analysis of Hardy Weinberg equilibrium (HWE) exposed that the genotypes were compatible with equilibrium in both PCa and control samples with no significant differences among frequencies of (observed and expected) in which (p > 0.05). Surveying for the relation of (rs 12329760) with both allele and genotype frequencies appeared that there were no major differences between patients and controls frequencies, although there were decreasing and increasing in the percentage of C allele (67 vs 72.8 %) and T allele (33 vs 27.2 %) respectively.